Sustainability Status Analysis of Urban Mangrove Management Using Multidimensional Scaling (MDS) Rapfish - Amalia, Yunita Suci; Khusaini, Mohammad; Atikawati, Dini; Hidayati, Bunga; Prismadianto, Gita (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Kebun Raya Mangrove Surabaya is an is an urban mangrove conservation ecotourism area. However, the rise in tourism activities, institutional limitations, and lack of proper facilities have become major issues in the area. This study aims to examine the status of discontinuation in the management of ecotourism areas using the multidimensional scaling (MDS) method within a rap-tourism framework. The analysis will cover 43 assessment attributes for five dimensions of tourism: ecology, economy, social, institutions, and infrastructure and technology. The findings of the study revealed that the sustainability index values are as follows: ecological (86.25), economic (63.52), social (89.13), institutional (84.51), and infrastructure and technology (88.07), all indicating high sustainability. The study found that this area has a sustainability index result with an overall average value of 82.30, which falls into the highly sustainable category. The findings suggest that Surabaya mangrove ecotourism is in good condition; however, improvements are needed, particularly in the economic dimension, which requires the most strengthening to maintain long-term sustainability.